+0  
 
+3
235
2
avatar+10 

Help please, Ill show work on what I got.. 3^2 + 2^2 = C^2 9 + 4 = C^2 13^2 = C^ (Pythagorean Theorem)

FrozenProGaming  Apr 24, 2017
 #1
avatar
+1

If you have: 3^2 + 2^2 = C^2, then:

9 + 4 = C^2

13 = C^2   Now, take the square root of both sides:

C = sqrt(13) = 3.61 (rounded).

Guest Apr 24, 2017
 #2
avatar+10 
0

Thxs.. That really worked out for me. thank you very much. 

FrozenProGaming  Apr 25, 2017

5 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.